PRINCIPLES OF CREATING THE MAIN CHARACTER IN O‘LMAS UMARBEKOV'S “QIZIMGA MAKTUBLAR” (International Educators Conference, 2025)
This article studies the role of epistolary prose in creating the main character in Uzbek People's Writer O‘lmas Umarbekov's work “Qizimga Maktublar” It analyzes how the father's letters to his daughter reveal his inner world, life views, and moral principles. The article also discusses the unique features of epistolary prose, the role of letters in shaping the character, and the main principles of creating the main character in the work. The research findings aim to highlight Umarbekov's skill, the potential of the epistolary genre, and the literary value of “Letters to My Daughter”.